Parametric analysis and design of compact omnidirectional and directional ultra-wideband antenna - Muslim, Suci Rahmatia (2011)
Ultra-wideband (UWB) is a promising Wireless Personal Area Network (WPAN) technology for transmitting data at very high rates using very low power within very wide bandwidth. UWB technology has the radio spectrum between 3.0 GHz to 10.6 GHz that covers the bandwidth from 20 to 200 percent greater than the size of the centre frequency determined by the Federal Communication Commission (FCC) and the Malaysian mmunications and Multimedia Commission (MCMC). UWB antenna is one of the main challenges in UWB system due to its significant role in achieving successful transmission and reception of information. This thesis presents two new designs UWB microstrip patch antenna using different substrates and produce different radiation patterns. Some simple techniques are used to modify the radiator patch and ground plane which aims to improve the impedance bandwidth and to achieve a stable radiation pattern. Both UWB antennas were developed and analyzed by a 3D electromagnetic computer aid simulator. To verify the simulation results, the Antenna#1 of Small Size Ultra-Wideband Planar Antenna with Semi-Elliptic Horn with Steps was fabricated on FR4 substrate with dielectric constant of 4.4 and the Antenna#2 of Planar Quasi-Parabolic Directional was fabricated on Rogers RT5870 substrate with dielectric constant of 2.33. The measurements performed using a vector network analyzer (VNA Anritsu 37347D), indicates a fairly good agreement between simulation and measurement. The simulation results of Antena#1 shows that this antenna has the operational bandwidth ranging from 3.45 GHz to 13.7 GHz with a return loss less than -10 dBs. Optimized size of antenna size is 29 x 29 x 1.6 mm3 with the radiation pattern is omnidirectional. While the simulation results of Antenna#2 shows that its operational bandwidth is ranging from 3.8 GHz to 10.5 GHz with a return loss better than -10 dBs. Optimized size of antenna size is 30 x 30 x 0.79 mm3 with directional radiation patterns. Moreover, both designed antennas exhibit high radiation efficiency and stable group delay which makes them suitable for UWB wireless communication applications.